On Gulzar’s Poetry: Comparing the Three Versions of English Translation - Pallavi Kiran (University of Chitral Journal of Linguistics and Literature, 2025)
Gulzar’s merit as a contemporary Indian poet rests on his use of Hindustani, which has a high degree of emotional intensity, expressiveness, naturalness and unusual vividness that strikes the head and the heart of the listener. The study pragmatically and stylistically probes a randomly selected poem of Gulzar and its English translation by three translators, underlining, in the main, the variations in the linguistic choices they make and the significant differences in their translation. The analysis discusses that which is complicated and complex in the poem; and how it is simplified by the translator, leaving out that which puzzles the poet. The pragmatic-stylistic approach effectively identifies the translation shifts and investigates the value and belief system of Gulzar encoded in the language.